Synthesis and evaluation of novel pyridine-, pyrimidine- and triazine-based derivatives as potential HIV-1 non-nucleoside reverse transcriptase inhibitors (NNRTIs) - Changunda, Charles Reuben K (My University, 2018)
As part of our goal to identify heterocyclic-based analogues that could act as allosteric inhibitors of the HIV-1 reverse transcriptase (RT) enzyme, small libraries of novel molecules containing pyridine, pyrimidine and triazine central cores were designed and synthesized for a preliminary in vitro assay against the wild-type RT virus. To achieve this goal, in the first instance we explored a scaffold-hopping approach as a possible strategy for identifying promising molecules. This scaffold-hopping approach primarily involved the “dismantlement” of an imidazo[1,2-a]pyridine central core of a potent anti-HIV novel compound previously identified in our research laboratory to generate 2,6-disubstituted pyridines. As discussed in chapter 2, we utilized the 2,6-disubstituted pyridine core as a platform for accessing a more conformationally flexible set of analogues in which the central pyridine core was connected to the chloro-substituted aromatic ring via an amido, amino or sulfonamido hetero-linker to generate the pyridyl-benzamide, pyridyl-benzylamine and pyridyl-sulfonamides scaffolds, respectively. The scaffolds were cross-coupled with selected nitrogen-, oxygen- and sulfur-containing nucleophiles via a palladium-mediated methodology to generate a small library of novel analogues for testing against the wild-type virus. One novel pyridyl-benzamide, 2-chloro-N-(6-(piperidin-1-yl)pyridin-2-yl)benzamide, showing excellent antiviral activity (IC50=0.7μM), was identified from whole-cell antiviral screening. The second approach, which is covered in chapter 3, used molecular modelling in the design of potential heterocyclic NNRTI compounds that resembled a DAPY-type horse-shoe framework. The approach involved in silico docking of di-functionalized pyridine- and tri-functionalized pyridine-, pyrimidine-, and triazine-based virtual analogues into the allosteric site of the reverse transcriptase enzyme crystal structure (pdb: 3MEG RT). The tri-functionalized pyridine-core containing amides emerged as top modelling hits with superior ligand-receptor interaction energies. In addition, these analogues also displayed a favourable binding conformation that targeted key hydrophobic (Tyr181, Tyr188, Phe227, Trp229, Leu234, Pro236, Tyr318) and hydrophilic interactions in the allosteric site of the 3MEG RT crystal structure and were synthesized via our already developed palladium-catalyzed methodology as candidates for a primary screen against the wild-type HI virus. Moreover, biocatalysis was also successfully applied for the selective hydrolysis of a pyridyl nitrile group to access one of the top modelling hit compounds, 6-(4-chlorophenoxy)-2-((2-cyano-5-methylphenyl)amino)nicotinamide as a key target for the antiviral screening. The scaffold hopping approach proved more rewarding as it led to the identification of a novel pyridyl-benzamide novel compound with excellent antiviral activity against the wild-type RT virus. This is the first such compound to be identified as displaying activity against RT. As discussed in chapter 4, novel pyridyl-benzamide and pyridyl-sulfonamide compounds that displayed reasonable antimicrobial activity (39 μg/ml) against two gram-positive bacteria, S. aureus and B. cereus, were also identified from an antimicrobial screen.
A Dissertation submitted to the Faculty of Science, University of the Witwatersrand, in fulfilment of the requirements of the Doctor of Philosophy Johannesburg, 2018
Keywords: HIV (Viruses)--Enzymes.; Antiviral agents; Medical microbiology